E-Government as Public Sector Innovation - Amanda, Natasha Firdha Putri (JPAS (Journal of Public Administration Studies), 2019)
Information and communication technologies (ICTs) have a critical role in public sector. The use of ICT in service innovation to citizens is known as e-government. E-government as public sector innovation presents a higher quality, cost-effective, government services and a better relationship between citizen and government. On the other hand study conducted by Lee (2009) show the implementation of e-government in many countries is not in line with expectations. The purpose of this paper is to discuss what factors influence the success of e-government as public sector innovation.This research used systematic literature review method to conduct a brief selective review of CSF (critical success factors) in implementing e-government. The outcome of the finding there are several critical success factors (CSF) that influence e-government as public sector innovations consist of planning, organizational structure, organizational culture, policy, human resources, leadership, communication, coordination and collaboration, and awareness. Thus defining CSF especially in implementing e-government will help public organizations avoid the failure of e-government projects.